Prevalence of Antenatal TORCH’ Infections by Serological detection in Cases of Poor Obstetric Outcome - Abeer, A.; D. Abdelmonem, M.; Hany, A.; O.G. Abdel-Hafeez, M.R.C. (Scientific Journal of Medical Science, 2014)
The TORCH test, which is sometimes called the TORCH panel, consists of tests for antibodies to four organisms that cause congenital infections transmitted from mother to fetus. The name of the test is an acronym for the organisms detected by this panel: Toxoplasma gondii (toxoplasmosis), rubella (German measles), cytomegalovirus (CMV), and herpes simplex virus (HSV). To determine the prevalence rates of IgM and IgG to common TORCH agents in pregnant women using indirect enzyme-linked immunosorbent assay in cases of poor obstetric outcome. A total of 950 samples of sera were tested for antibodies to TORCH agents known to cause serious congenital infections: Toxoplasma gondii, rubella, cytomegalovirus (CMV), Rubella, herpes simplex viruses. In our study, out of 950 pregnant women, a total of 220 (23.1%) were positive for IgM Rubella and a total of 550 (57.8%) were positive for IgG Rubella. Toxoplasma IgM positive were 66 (6.9%), Toxoplasma IgG positive were 380 (40%), CMV IgM positive were 65 (6.8 %) CMV IgG positive were 890 (93.6 %) and 25 (2.6%) were positive for HSV II for IgM and 320 (33.6%) were positive HSV II for IgG . All antenatal cases with poor obstetric outcome should be routinely screened for TORCH as early diagnosis and appropriate intervention, will help in proper management of these cases. Some of pregnant women commonly have IgG antibodies to CMV followed by rubella, and then T. gondii, and the last one HSV.